2020
DOI: 10.1038/s41598-020-68452-x
|View full text |Cite
|
Sign up to set email alerts
|

Confirming the geography of fatty infiltration in the deep cervical extensor muscles in whiplash recovery

Abstract: Previous preliminary work mapped the distribution of neck muscle fat infiltration (MFI) in the deep cervical extensor muscles (multifidus and semispinalis cervicis) in a small cohort of participants with chronic whiplash associated disorders (WAD), recovered, and healthy controls. While MFI was reported to be concentrated in the medial portion of the muscles in all participants, the magnitude was significantly greater in those with chronic WAD. This study aims to confirm these results in a prospective fashion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…MRI findings of altered muscle adiposity are present across a number of spinal pathologies. For example, patients with severe WAD have higher MFI in cervical flexors and extensors as compared to healthy controls and patients with mild/moderate WAD [ 15 19 ]. Elevated levels of MFI in chronic whiplash may be reduced through a regimen of neck specific exercises [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI findings of altered muscle adiposity are present across a number of spinal pathologies. For example, patients with severe WAD have higher MFI in cervical flexors and extensors as compared to healthy controls and patients with mild/moderate WAD [ 15 19 ]. Elevated levels of MFI in chronic whiplash may be reduced through a regimen of neck specific exercises [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that MFI may be an important pathophysiological marker in variety of conditions affecting the appendicular skeleton and the axial spine such as rotator cuff injury [ 40 42 ], WAD [ 15 19 ], disc herniation [ 43 , 44 ], degenerative disc disease [ 45 ], and DCM [ 14 ], respectively. However, studies on comprehensive examination of cervical muscle composition and its effects on symptomology, diagnostic, and prognostic utility in patients in DCM are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the pathophysiological and pathomechanical mechanisms underlying these spinal conditions differ, the characteristic pattern of MFI appears to occur with greatest magnitude in the deep muscular layers of the cervical extensors (i.e., multifidus and semispinalis cervicis (MFSS)) and cervical flexors (i.e. longus colli and longus capitis (LC)) [18][19][20] . The ubiquitous nature of muscle compositional changes in these spinal conditions suggests MFI may be one common biological explanation or risk factor for persisting neck-related disability.…”
Section: Trmentioning
confidence: 99%
“…In addition to microRNAs as blood-based predictors of adverse posttraumatic outcomes, substantial research efforts have focused on understanding the contribution of skeletal muscle changes to post-trauma recovery, including how fatty infiltration of cervical muscle (MFI) influences tissue/stress injuries in the neck [27][28][29][30][31][32][33] . Recent longitudinal studies have demonstrated that MFI is predictive of 28 and associated with [31][32][33][34] PNPD, yet the molecular mechanisms mediating this association are not yet clear.…”
mentioning
confidence: 99%